Upaya Guru Akidah Akhlak Dalam Mengembangkan Modul Pembelajaran Akidah Akhlak di Madrasah Aliyah Nurul Cholil Kabupaten Bangkalan - Muhammad Yusron Maulana El-Yunusi; Amatillah Thaha; Hamimuddin Hamimuddin (Departement of Mathematics Education, 2023)
Learning difficulties experienced by students can certainly be a great task for a teacher who is entrusted with the responsibility for the students. Learning activities do not always run smoothly and as desired, sometimes they run smoothly or even very obstructed in various situations and conditions. Obstacles and constraints that occur are not only experienced by students as recipients of material but also by educators or teachers who inevitably feel some obstacles in presenting the material. The purpose of this study is for teachers to be able to overcome various obstacles and barriers felt during the learning process. In this study, the author examines the efforts of Akidah Akhlak teachers in developing Akidah Akhlak learning modules in order to create an effective and conducive learning environment. This research uses a literature review and qualitative research method with a case study approach. The results of this scientific study are that there are several efforts by Akidah Akhlak teachers in developing Akidah Akhlak learning modules, namely by developing technology-based teaching materials, presenting material as interesting as possible by utilizing the use of PPT or displaying short videos related to the material and by using a group approach such as discussing material so that students can have a deeper understanding and mastery of the material. This is done by following various IPTEK training and holding several seminars and talk shows.